USE OF LONG TERM CARE AND HEALTH SERVICES – WHAT DIFFERENCE DOES WEALTH MAKE?. (16th November 2018) - Spiers, G; Hanratty, B; Matthews, F; Moffatt, S; Kingston, A; ,
Abstract: Long-term care helps to maintain independence in older age. Older adults who are too wealthy to qualify for state or federal subsidised care, but not wealthy enough to pay for their own care, may be particularly disadvantaged. Evidence shows that poor access to long term care may influence older adults' use of health services. This research explored the moderating role of wealth in the relationship between older adults' use of social care and healthcare utilization, in a country where healthcare was free at the point of access. Data were drawn from the Newcastle 85+ study, a cohort of 85 year olds initiated in 2006 in Newcastle-upon Tyne, England (n=849). Variables for wealth, social care use and healthcare use were created from baseline data. Linear regression was used to model the association between social care and healthcare use, and an interaction explored the moderating role of wealth. High social care use was associated with a lower healthcare use score (coef= -0.74, 95% CI: -1.34, -0.13), when compared to low social care use. A number of candidate models will be presented, and evidence of how this relationship changes according to levels of wealth will be discussed. As populations age, high-income countries must ensure older people have equitable access to long-term care, regardless of their material circumstances. Policy implications for older adults' equitable access to long-term care and the potential consequences for healthcare utilization will be discussed.